Orientia tsutsugamushi Nucleomodulin Ank13 Exploits the RaDAR Nuclear Import Pathway To Modulate Host Cell Transcription - Haley E. Adcox (American Society for Microbiology, 2021)
ABSTRACT Orientia tsutsugamushi is the etiologic agent of scrub typhus, the deadliest of all diseases caused by obligate intracellular bacteria. Nucleomodulins, bacterial effectors that dysregulate eukaryotic transcription, are being increasingly recognized as key virulence factors. How they translocate into the nucleus and their functionally essential domains are poorly defined. We demonstrate that Ank13, an O. tsutsugamushi effector conserved among clinical isolates and expressed during infection, localizes to the nucleus in an importin β1-independent manner. Rather, Ank13 nucleotropism requires an isoleucine at the thirteenth position of its fourth ankyrin repeat, consistent with utilization of eukaryotic RaDAR (RanGDP-ankyrin repeats) nuclear import. RNA-seq analyses of cells expressing green fluorescent protein (GFP)-tagged Ank13, nucleotropism-deficient Ank13I127R, or Ank13ΔF-box, which lacks the F-box domain essential for interacting with SCF ubiquitin ligase, revealed Ank13 to be a nucleomodulin that predominantly downregulates transcription of more than 2,000 genes. Its ability to do so involves its nucleotropism and F-box in synergistic and mutually exclusive manners. Ank13 also acts in the cytoplasm to dysregulate smaller cohorts of genes. The effector’s toxicity in yeast heavily depends on its F-box and less so on its nucleotropism. Genes negatively regulated by Ank13 include those involved in the inflammatory response, transcriptional control, and epigenetics. Importantly, the majority of genes that GFP-Ank13 most strongly downregulates are quiescent or repressed in O. tsutsugamushi-infected cells when Ank13 expression is strongest. Ank13 is the first nucleomodulin identified to coopt RaDAR and a multifaceted effector that functions in the nucleus and cytoplasm via F-box-dependent and -independent mechanisms to globally reprogram host cell transcription. IMPORTANCE Nucleomodulins are recently defined effectors used by diverse intracellular bacteria to manipulate eukaryotic gene expression and convert host cells into hospitable niches. How nucleomodulins enter the nucleus, their functional domains, and the genes that they modulate are incompletely characterized. Orientia tsutsugamushi is an intracellular bacterial pathogen that causes scrub typhus, which can be fatal. O. tsutsugamushi Ank13 is the first example of a microbial protein that coopts eukaryotic RaDAR (RanGDP-ankyrin repeats) nuclear import. It dysregulates expression of a multitude of host genes with those involved in transcriptional control and the inflammatory response being among the most prominent. Ank13 does so via mechanisms that are dependent and independent of both its nucleotropism and eukaryotic-like F-box domain that interfaces with ubiquitin ligase machinery. Nearly all the genes most strongly downregulated by ectopically expressed Ank13 are repressed in O. tsutsugamushi-infected cells, implicating its importance for intracellular colonization and scrub typhus molecular pathogenesis.